Analisis Kinerja Keuangan Perbankan Syariah Sebelum dan Sesudah Merger di Indonesia - Muchran, Muchriana; Kirana, Anggi; Nasrullah , Nasrullah (Al-Buhuts, 2023)
Abstract This study aims to examine the  differences in  the financial  performance of  Bank Syariah  Indonesia (BSI) before and after the merger. This research uses a type of quantitative research with a descriptive approach. The analytical method used in this study is descriptive analysis test, hypothesis  testing with the Paired Sample T-test and the Wilcoxon test. The results of this study indicate that Return On Assets (ROA) does not indicate any difference between before and after the merger. Return On Equity (ROE) does not show any difference between before and after the merger. Total Asset Turn Over (TATO) does not show any difference between before and after the merger. Net Profit Margin (NPM) shows the difference between before and after the merger. The Financial Leverage Multiplier (FLM) does not show any difference between before and after the merger